Highly selective and sensitive detection of Cr6+ ions using size-specific label-free gold nanoparticles - Kanagaraj, Rajalakshmi; Nam, Yun-Sik; Pai, Sung Jin; Han, Sang Soo; Lee, Kang-Bong (ELSEVIER SCIENCE SA, 2017)
Gold nanoparticles (AuNPs) of various sizes were synthesized by modifying the citrate concentration; 45 nm AuNPs were found to respond to Cr6+ ions selectively. Label-free AuNPs, 45 nm, showed localized surface plasmon resonance bands at 530 nm, which decreased linearly upon addition of Cr6+. The addition of Cr6+ also resulted in the appearance of a new band at 750 nm, along with a visible color change in the solution from wine red to violet. The decrease in absorbance and color change were due to AuNP aggregation upon coordination of Cr6+. The detection limit for Cr6+ was 0.4 nM, and excellent selectivity was observed in the presence of other metal ions and anions. The binding site and sensing mechanism for Cr6+ and label-free AuNPs were characterized by X-ray photoelectron spectroscopy and time-of-flight secondary ion mass spectrometry. This method was applied to tap, pond, and waste water samples, and validated using inductively coupled plasma-optical emission spectrometry, illustrating the utility of thes ensitive, selective, and simple AuNP sensor in the detection of Cr6+. (C) 2017 Elsevier B. V. All rights reserved.
Keywords: COLORIMETRIC DETECTION; CHROMIUM; CR(VI); SPECTROMETRY; SAMPLES; WATER